Dampak Keberadaan Go Food Dan Grab Food Terhadap Peningkatan Penjualan Usaha Kuliner Di Kota Metro - Suwarto; Suryadi; Trihadi Hermansyah (Universitas Muhammadiyah Metro, 2024)
The development of technology and information plays an important role in economic growth. Today, technology and information are needed, including in the culinary business. The presence of Go Food and Grab Food services, which are food delivery features for food delivery developed by the Gojek and Grab applications, really help culinary entrepreneurs run their businesses. This study aims to find out how the impact of the existence of Go Food and Grab Food, how to increase sales of culinary businesses in Metro City after joining Go Food and Grab Food. The type of research used by the author is field research, using a qualitative approach. The techniques used in collecting data in this study include observation, interviews and documentation. The data analysis technique used in this study is inductive. The population in this study are business people who join Go Food and Grab Food in Metro City. Data collection was carried out through interviews with 5 culinary entrepreneurs in Metro City. The research results show that the existence of Go Food and Grab Food is very helpful for culinary entrepreneurs in the form of marketing and increasing sales. Culinary business people stated that there was an increase in sales after joining Go Food and Grab Food services.